Conceptual design and aerodynamic study of blended wing body business jet - Djojodihardjo, Harijono; Kek, Alvin Leong Wei (2012)
A Conceptual Design and Aerodynamic Study of Business Jet BWB Aircraft is carried out focusing on BWB Aerodynamics, including Wing Planform Configuration and profiles, and their relationship to the Design Requirements and Objectives. Possible Configuration Variants, Mission profile, Flight Envelope requirements, performance, stability, as well as the influence of propulsion configuration and noise considerations of BWB aircrafts are considered and elaborated. Parametric study performed on wing planform, thickness, and twist optimization, with design variables including overall span plus chord, sweep, thickness, and twist at several stations along the span of the wing prior to more structured optimization scheme. Considerations are also given to range, trim, structural design, maximum lift, stability, control power, weight and balance. A statistical study and review on prevailing market demand lead to the choice of a candidate of conventional Subsonic Business Jet, which will be used as a baseline for the aerodynamic and configuration conceptual design. The chosen business jet accommodates 10 passengers as a baseline. Some aerodynamic and performance improvement is then carried out through parametric study to arrive at the best solution meeting the design requirements and objectives.